All Arthroscopic Suprapectoral Biceps Tenodesis - Joseph A. S. McCahon DO; Mohamed F. Albana DO; Patrick F. Szukics DO; Sean McMillan DO (SAGE Publishing, 2022)
Background: Biceps tendinopathy can have significant clinical manifestations in active patients. Failure to achieve resolution of symptoms through nonsurgical modalities oftentimes results in surgical intervention. The 2 most common surgical treatment options for tendinopathy of the long head of the biceps tendon (LHBT) are tenotomy and tenodesis. Both modalities have shown efficacy within the literature; however, tenodesis of the LHBT has many advantages to tenotomy. Indications: Subgroove tenodesis eliminates the potential pain generation within the bicipital groove. Despite recent proof of clinical equivalence in open versus arthroscopic tenodesis, there has been increasing interest in all-arthroscopic biceps tenodesis techniques in hopes of minimizing surgical exposure, decreasing the rate of potential neurovascular compromise, and decreasing the time to recovery. Technique: We present an all-arthroscopic technique for a subgroove biceps tenodesis using a unicortical tensionable button. The proximal biceps anchor is held in place at its insertion site with a spinal needle to prevent retraction. The lateral portal is redirected into the subdeltoid space. A novel suprapectoral biceps portal, called the Willingboro portal, is placed percutaneously 2 cm above the pectoralis tendon. Onlay fixation of the LHBT is performed proximal to the pectoralis major muscle insertion using a unicortical button. Postoperative protocol is similar to other fixation constructs. Results: Numerous arthroscopic biceps tenodesis techniques have been described with good success; however, an all-arthroscopic suprapectoral tenodesis is attractive to many reasons. The unicortical button construct shows similar load to failure strength as the bicortical button construct, both of which are greater than all other constructs described in the literature. Discussion/Conclusion: Arthroscopic subgroove biceps tenodesis using a unicortical button technique is a viable option that avoids the complications associated with an open axillary incision as well as persistent groove pain. Anchoring the biceps tendon prior to tenotomy allows for preservation of tendon length, limiting the complications associated with tendon retraction with anticipated improvement in patient-reported outcomes. The unicortical button is known to have a similar strength profile as the bicortical button technique, which is greater than other techniques described in the literature. Future studies should be aimed at assessing long-term patient-reported outcomes. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.